2015
DOI: 10.1104/pp.15.00659
|View full text |Cite
|
Sign up to set email alerts
|

Multilayered Regulation of Ethylene Induction Plays a Positive Role in Arabidopsis Resistance against Pseudomonas syringae

Abstract: Ethylene, a key phytohormone involved in plant-pathogen interaction, plays a positive role in plant resistance against fungal pathogens. However, its function in plant bacterial resistance remains unclear. Here, we report a detailed analysis of ethylene induction in Arabidopsis (Arabidopsis thaliana) in response to Pseudomonas syringae pv tomato DC3000 (Pst). Ethylene biosynthesis is highly induced in both pathogen/microbe-associated molecular pattern (PAMP)-triggered immunity and effector-triggered immunity (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
90
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 94 publications
(94 citation statements)
references
References 75 publications
4
90
0
Order By: Relevance
“…It is induced by pathogen attack and environmental stimuli such as wounding, flooding, heavy metal stress, or ozone exposure (Moeder et al , ; Nie et al , ; Rao et al , ; Keunen et al , ). For example, ACS2 and ACS6 are required for ET induction by flg22 (Liu and Zhang, ; Guan et al , ) and the heavy metal chromium (Schellingen et al , ). In our previous study, Cu 2+ promoted the transcription of the AtACS8 gene to induce ET production (Zhang et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…It is induced by pathogen attack and environmental stimuli such as wounding, flooding, heavy metal stress, or ozone exposure (Moeder et al , ; Nie et al , ; Rao et al , ; Keunen et al , ). For example, ACS2 and ACS6 are required for ET induction by flg22 (Liu and Zhang, ; Guan et al , ) and the heavy metal chromium (Schellingen et al , ). In our previous study, Cu 2+ promoted the transcription of the AtACS8 gene to induce ET production (Zhang et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…In search of the underlying mechanisms of MPK3/MPK6 in plant immunity, we found that MPK3/MPK6 regulate the biosynthesis of ethylene, an important plant stress hormone (Kim et al, 2003;Liu and Zhang, 2004;Joo et al, 2008;Han et al, 2010;Li et al, 2012;Guan et al, 2015), and camalexin, the major phytoalexin in Arabidopsis (Ren et al, 2008;Mao et al, 2011). Recently, a metabolomic analysis demonstrated that gain-of-function activation of MPK3/MPK6 reprograms defense metabolism, including camalexin and IGS (Lassowskat et al, 2014;Lee et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Altogether, ACC (the precursor of ET) and ET could act as the signaling molecules under stressful conditions and the high level of ERF gene expression could be efficient response led to decrease high levels of ACC and ET in leaf tissues. In the same way, Guan et al [53] revealed that Arabidopsis mutants in ACC Synthase (defect in ET production) showed greater susceptibility to P. syringae infection. The observations proposed that ERF gene in leaf tissue was more strongly up-regulated in IT20+SS14 than plants only inoculated with IT20.…”
Section: Plos Onementioning
confidence: 83%